The survivors - Weaver, Will. (New York : Harper, 2012)
Sixteen-year-old Miles, thirteen-year-old Sarah, and their parents find themselves changing in many ways as they struggle to survive winter in a remote cabin, while keeping anyone in the nearby town from learning they are living there illegally after the devastation of volcanic eruptions drove them from their Minneapolis home.
Sequel to: Memory boy
Keywords: Wilderness survival -- Fiction; Family life -- Minnesota -- Fiction; Minnesota -- Fiction; Wilderness survival -- Juvenile fiction; Families -- Juvenile fiction; Minnesota -- Juvenile fiction